Preferred Leadership Styles Within Minor League Baseball Organizations’ Front Offices - Davis, Danny; Gagnon, Max Blaisdell; Fiorentino, Leah Holland; Wooten, Marian H. (European Scientific Journal, ESJ, 2017)
Due to the importance of leadership within athletics, this study set out to measure self-reported preference of leadership styles within Minor League Baseball (MiLB) organizations’ front offices. The Revised Leadership Scale for Sport (RLSS) was administered to MiLB front office employees at the AAA and AA levels. This instrument previously had been used to measure current athletes’ preferences for their coaches’ leadership styles. Four hypotheses focused on respondents’ preferences for their supervisors’ uses of autocratic and democratic leadership styles based on respondents’ gender and history with team or individual sport competition. Hypothesis testing revealed only one significant finding, that male front office employees had a higher preference for autocratic leadership style than did female front office employees.